Transfer Student-Athletes: Prominent but Vulnerable - Bunnage, Joanne C.; Rice, Robert L. (My University, 1991)
Transfer students play a prominent role in Division I athletics, but the effects of transferring can often be detrimental to their academic performance. Providing a formal orientation course especially designed for new transfer student-athletes can be an effective means of helping them bridge the intercollegiate experience. This gives an example transfer orientation program from Oregon State University.
Keywords: transitions; models